Formulasi salep ekstrak etanol daun cocor bebek (Kalanchoe pinnata Lamk.) dengan basis cera dan vaselin album - Retnowati, Eko; Hasanatin, Sitta; Setyaningsih, Dewi (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2023)
ABSTRACT The ethanol extract of the leaves of cocor bebek (Kalanchoe pinnata Lamk.) with a concentration of 20% have antibacterial activity. This study aims to determine the physical characteristics of the ethanol extract of cocor duck leaf ointment based on a combination of Cera alba and Vaseline album. The method used in this research is the maceration method using 70% ethanol and the extract concentration used in each formula is 20%. The ointment was made in 5 formulas with a combination of Cera alba and Vaseline album of Fl (5.95), FII (10 90), FIII (15 85), FIV (20 80), FV (25 75). The ointment was tested for physical characteristics including: organoleptic, homogeneity, viscosity, spreadability, adhesion, and pH. The results of the organoleptic and homogeneity tests were analyzed descriptively, while data on dispersion and adhesion were analyzed statistically by one-way ANOVA parametric with a 95% confidence level followed by the Tuckey test, while the viscosity and pH values ​​were analyzed non-parametric statistics using Kruskal Wallis followed by Mann Whitney test. Based on the results showed that the combination of cera alba-vaceline album base produced a homogeneous ointment with different characteristics in viscosity, adhesion, spreadability and pH. Keywords: Ethanol extract, Kalanchoe pinnata, ointment, cera alba, vaseline album   ABSTRAK Ekstrak etanol daun cocor bebek (Kalanchoe pinnata Lamk.) dengan kadar 20% telah terbukti memiliki aktivitas sebagai antibakteri. Penelitian ini bertujuan untuk mengetahui karakteristik fisik salep ekstrak etanol daun cocor bebek dengan basis kombinasi cera alba dan vaselin album. Metode yang digunakan dalam penelitian ini adalah metode maserasi menggunakan etanol 70% dan konsentrasi ekstrak yang digunakan dalam tiap formula sebesar 20%. Salep dibuat sebanyak 5 formula dengan kombinasi cera alba:vaselin album yaitu Fl (5:95), FII (10:90), FIII (15:85), FIV (20:80), FV (25:75). Salep diuji karakteristik fisiknya meliputi: organoleptis, homogenitas, viskositas, daya sebar, daya lekat, dan pH. Hasil uji organoleptis dan homogenitas dianalisis secara deskriptif, sedangkan data pada daya sebar dan daya lekat dianalisis secara statistik parametrik Anova satu jalan dengan taraf kepercayaan 95% dilanjutkan uji Tuckey, sedangkan viskositas dan nilai pH dianalisis secara statistik non parametrik menggunakan Kruskal Wallis dilanjutkan dengan uji Mann Whitney. Berdasarkan Hasil penelitian menunjukkan bahwa kombinasi basis cera alba-vaselin album menghasilkan salep yang homogen dengan karakteristik yang berbeda pada viskositas, daya lekat, daya sebar dan pH. Kata Kunci: Ekstrak etanol, Kalanchoe pinnata, salep, cera alba, vaselin album